2014
DOI: 10.1371/journal.pone.0106840
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Developing Hyponatremia in Thyroid Cancer Patients Undergoing Radioactive Iodine Therapy

Abstract: BackgroundDue to the alarming increase in the incidence of thyroid cancer worldwide, more patients are receiving postoperative radioactive iodine (RAI) therapy and these patients are given a low-iodine diet along with levothyroxine withdrawal to induce a hypothyroid state to maximize the uptake of RAI by thyroid tissues. Recently, the reported cases of patients suffering from life-threatening severe hyponatremia following postoperative RAI therapy have increased. This study aimed to systematically assess risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…However, despite the relatively high prevalence of post-RAI hyponatremia, there was still no significant correlation noted between post-RAI sodium concentrations and TSH levels. This is consistent with a previous study done by Hammami et al [ 2 ] and Lee et al [ 4 ], wherein they also noted no significant correlation between post-isolation sodium concentration and TSH levels. It was concluded in the previous studies that the association between clinically-significant hyponatremia and hypothyroidism may be due to restricted to chronic uncorrected hypothyroidism [ 2 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, despite the relatively high prevalence of post-RAI hyponatremia, there was still no significant correlation noted between post-RAI sodium concentrations and TSH levels. This is consistent with a previous study done by Hammami et al [ 2 ] and Lee et al [ 4 ], wherein they also noted no significant correlation between post-isolation sodium concentration and TSH levels. It was concluded in the previous studies that the association between clinically-significant hyponatremia and hypothyroidism may be due to restricted to chronic uncorrected hypothyroidism [ 2 ].…”
Section: Discussionsupporting
confidence: 93%
“…This occurred at approximately 4 weeks after thyroid hormone withdrawal and 2 weeks after low iodine diet, respectively. The incidence and magnitude of hyponatremia, the severity of hypothyroidism, old age (more than 60 years old) proposed as risk factors for developing hyponatremia after RAI therapy [ 4 5 ]. Case reports of life-threatening hyponatremia developing in hypothyroid patients have also been reported, either due to post-surgical hypothyroidism or levothyroxine withdrawal; however, its prevalence has not been well established in this population [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] The largest study including 2229 patients reported moderate to severe hyponatremia in 2% of patients and reported old age, female sex, use of thiazide diuretics, and hyponatremia at the initiation of RAI therapy as independent risk factors for the development of hyponatremia. 19 The study is limited by its retrospective nature. Moreover, the study does not provide the prevalence of renal dysfunction across wide range of thyroid function tests since it included only those patients with TSH >40 µIU/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Pre‐ablation serum sodium levels were within normal limits in all cases, and the hyponatraemia developed between 2 and 12 days following cessation of the LID. Additionally, in a retrospective study of 2229 patients with DTC who underwent 2‐week LID with THW prior to RAI ablation, 2·0% were found to have moderate to severe hyponatraemia (serum sodium <130 mEq/l) within 7 days after RAI ablation . Multivariate analyses showed that old age, female sex, use of thiazide diuretics and hyponatraemia at the initiation of RAI ablation independently predicted hyponatraemia after ablation.…”
Section: Methodsmentioning
confidence: 99%
“…did not observe severe hyponatraemia prior to RAI ablation, as the mean onset of severe hyponatraemia (<120 mEq/l) was 2·3 days following ablation. The authors proposed that increased oral fluid intake during RAI ablation to flush out the iodine may have contributed to and could explain the greater disturbances in serum sodium concentration after ablation …”
Section: Methodsmentioning
confidence: 99%